Preoperative Biliary Drainage in Cases of Borderline Resectable Pancreatic Cancer Treated with Neoadjuvant Chemotherapy and Surgery - Tomofumi Tsuboi; Tamito Sasaki; Masahiro Serikawa; Yasutaka Ishii; Teruo Mouri; Akinori Shimizu; Keisuke Kurihara; Yumiko Tatsukawa; Eisuke Miyaki; Ryota Kawamura; Ken Tsushima; Yoshiaki Murakami; et al. (Gastroenterology Research and Practice)
Objective. To elucidate the optimum preoperative biliary drainage method for patients with pancreatic cancer treated with neoadjuvant chemotherapy (NAC). Material and Methods. From January 2010 through December 2014, 20 patients with borderline resectable pancreatic cancer underwent preoperative biliary drainage and NAC with a plastic or metallic stent and received NAC at Hiroshima University Hospital. We retrospectively analyzed delayed NAC and complication rates due to biliary drainage, effect of stent type on perioperative factors, and hospitalization costs from diagnosis to surgery. Results. There were 11 cases of preoperative biliary drainage with plastic stents and nine metallic stents. The median age was 64.5 years; delayed NAC occurred in 9 cases with plastic stent and 1 case with metallic stent (p=0.01). The complication rates due to biliary drainage were 0% (0/9) with metallic stents and 72.7% (8/11) with plastic stents (p=0.01). Cumulative rates of complications determined with the Kaplan-Meier method on day 90 were 60% with plastic stents and 0% with metallic stents (log-rank test, p=0.012). There were no significant differences between group in perioperative factors or hospitalization costs from diagnosis to surgery. Conclusions. Metallic stent implantation may be effective for preoperative biliary drainage for pancreatic cancer treated with NAC.